2021
DOI: 10.1155/2021/5888783
|View full text |Cite
|
Sign up to set email alerts
|

Value of Peak Expiratory Flow Rate in Evaluating Cough Ability in Patients Undergoing Lung Surgery

Abstract: Introduction. Postoperative ineffective cough is easy to occur after thoracic surgery, and it is also a risk factor for postoperative pulmonary complications (PPCs). Objectives. To explore the value of peak expiratory flow rate (PEF) in evaluating cough ability in patients undergoing lung surgery and evaluate the effectiveness of chest wall compression during the expiratory phase by PEF. Methods. From September 2020 to May 2021, the researchers collected the data of patients who underwent lung surgery. Eventua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…CPF has primarily been studied in patients with neuromuscular diseases and to predict the success of extubation in intensive care unit patients ( 27 ). Patients undergoing lung resection surgery experience a restrictive syndrome in the postoperative period due to the involvement of both the thoracic wall and lung parenchyma ( 28 ). Additionally, unilateral left vocal cord paralysis is a relatively common comorbidity in lung surgery ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…CPF has primarily been studied in patients with neuromuscular diseases and to predict the success of extubation in intensive care unit patients ( 27 ). Patients undergoing lung resection surgery experience a restrictive syndrome in the postoperative period due to the involvement of both the thoracic wall and lung parenchyma ( 28 ). Additionally, unilateral left vocal cord paralysis is a relatively common comorbidity in lung surgery ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…The study reported that 85% of patients with ALS would develop dysphagia and impaired secretion management, leading to impairment of mucociliary clearing and airway protection (6), which resulted in malnutrition, dehydration, and aspiration pneumonia (7). PEF can be used as a tool for assessing cough ability for patients who underwent lung surgery (8), pulmonary function assessment before lung surgery (9,10), and airway clearance in neurodegenerative disease (11). Recent studies reported that respiratory impairments in patients with ALS demonstrated reduced peak expiratory flow (PEF) rates compared to healthy controls (12,13), implying that PEF may be a good screen tool for identifying patients with ALS at risk for aspiration (13).…”
Section: Introductionmentioning
confidence: 99%